Analysis of Legal Certainty and Protection for Investors for Investment Refunds in Commercial Property Sale and Purchase Agreements - Ribel Sri Pipit Putri Zega; Muhammad Arif Prasetyo; Rodiatun Adawiyah (Ekasakti Journal of Law and Justice, 2026)
This study aims to analyze legal certainty and protection for investors for the return of investment funds in commercial property sale and purchase agreements, as well as examine the judges' legal considerations in Supreme Court Decision Number 5648 K/Pdt/2025. The research uses normative legal methods with legislative, conceptual, and case approaches. The source of legal materials consists of primary, secondary, and tertiary legal materials that are analyzed qualitatively. The results of the study show that legal certainty for the return of investment funds has a juridical basis in the Civil Code through the principles of pacta sunt servanda, default, compensation, and cancellation of agreements. Legal protection for investors can be provided preventively through clear agreements, examination of the legality of objects, and security of funds, and repressively through default lawsuits, refund demands, compensation, and the implementation of court decisions. Supreme Court Decision Number 5648 K/Pdt/2025 applies the principle ne bis in idem because of the similarity of subjects, objects, and subject matter with previous disputes that have permanent legal force. The application of this principle provides legal certainty and prevents repetition of cases, but has implications for the closure of investors' opportunities to refile investment refund claims. Therefore, investor prudence and strengthening regulations in the commercial property sector are needed to ensure more effective legal protection.